Manajemen Konflik dalam Meningkatkan Kinerja Pendidik dan Tenaga Kependidikan di SDN Lidah Wetan IV Surabaya - Alif, Muhammad Nur; Putra, Kevin Widyadhana Alianto; Damasaziz, Iknas Adijati Nugraha (Lembaga Yasin AlSys, 2024)
Conflict is something or an event that everyone in this world has experienced. Conflict management is a process where the conflicting parties or third parties design conflict strategies and use them to resolve the conflict in order to achieve the desired solution. The aim of this research is to determine conflict management and the welfare of educators and education staff at SDN Lidah Wetan IV. This research uses a qualitative approach with data collection techniques of observation, interviews, question and answer and documentation. The results obtained from this research are 1) the way the school handles conflicts between educators or educational staff. 2) steps taken by the school to prevent conflicts between educators and education staff.